Influenza Virus Neuraminidase Structure and Functions - McAuley, Julie L.; Gilbertson, Brad P.; Trifkovic, Sanja; Brown, Lorena E.; McKimm-Breschkin, Jennifer L. (Frontiers in Microbiology, 2019)
With the constant threat of emergence of a novel influenza virus pandemic, there must be continued evaluation of the molecular mechanisms that contribute to virulence. Although the influenza A virus surface glycoprotein neuraminidase (NA) has been studied mainly in the context of its role in viral release from cells, accumulating evidence suggests it plays an important, multifunctional role in virus infection and fitness. This review investigates the various structural features of NA, linking these with functional outcomes in viral replication. The contribution of evolving NA activity to viral attachment, entry and release of virions from infected cells and to maintenance of functional balance with the viral haemagglutinin is also discussed. Greater insight into the role of this important antiviral drug target is warranted.